CONTROL OF PLANT HEIGHT BY HETEROTRIMERIC G-PROTEIN ΑLPHA SUBUNIT IN RICE - Y. Chen; J. Wei; Y. Zhang; G. Li; B. Lü; L. Liu1 (Journal of Animal and Plant Sciences, 2021)
Plant height is an important agronomic trait in rice that affects rice morphogenesis, apical dominance, harvest index and yield. Rice plant height is controlled by genes that lie in a complex regulatory network. At present, many plant height-related genes have been identified in rice, among which heterotrimeric G-protein α subunit, RGA1, is an important regulator. RGA1 is involved in cell division and regulates internode cell number, and in the biosynthesis and responses to phytohormones gibberellin (GA) and brassinosteroid (BR) signalling that regulates stem and internode elongation. Additionally, RGA1 affects rice plant height via the effect on nitrogen uptake and utilization and the interaction with drought stress responses. This review summarizes the progress on the regulation of rice plant height by RGA1 and proposes a focus of future research on the influence of RGA1 on rice plant height. We hope to provide a theoretical foundation for elucidating the regulatory mechanism of plant height and the application of RGA1 in the genetic improvement of plant height for a high and stable grain yield in rice production. We also propose new ideas for revealing the integral functions of G-proteins in rice.
Keywords: RGA1; Plant height; Hormone; Nitrogen; Drought; Rice